Precordial ST Segment Depression on Admission Electrocardiogram as a Simple Noninvasive Tool for Predicting Coronary Artery Disease Complexity in Patients with Inferior Myocardial Infarction - Jaya Suganti; Anggia Chairuddin Lubis; Abdullah Afif Siregar; Andika Sitepu; Cut Aryfa Andra; Ali Nafiah Nasution; Harris Hasan (The Indonesian Heart Association, 2019)
Precordial ST Segment Depression on Admission Electrocardiogram as a Simple Noninvasive Tool for Predicting Coronary Artery Disease Complexity in Patients with Inferior Myocardial Infarction Jaya Suganti, Anggia Chairuddin Lubis, Abdullah Afif Siregar, Andika Sitepu, Cut Aryfa Andra, Ali Nafiah Nasution, Harris Hasan Department of Cardiology and Vascular Medicine, Faculty of Medicine University of Sumatera Utara, Haji Adam Malik General Hospital, Medan, Indonesia Background: Whether a precordial ST segment depression (PSTD) is merely a benign electrical phenomena or a sign of multivessel coronary artery disease (MVCAD) in inferior myocardial infarction (MI) remains unclear. The objective of this study is to analyze the complexity of coronary artery disease (CAD) in inferior MI patients with PSTD and to investigate whether PSTD can be used as a predictor of MVCAD in inferior MI. Methods: Patients with inferior MI were divided into two groups based on the presence of PSTD on admission ECG and were compared based on the patient’s coronary artery complexities. Results: A total of 215 patients with inferior MI were found in this study period, with 102 patients meet the inclusion and exclusion criteria. Patients with PSTD had a higher incidence of MVCAD and SYNTAX score. Further analyzes showed PSTD on admission ECG was an independent predictor of MVCAD in inferior MI [45 (66%) vs 23 (34%); OR 4.097; 95% CI 1.638-10.247; p=0.003). Conclusion: In daily clinical practice, PSTD on admission ECG may serve as a simple noninvasive tool for predicting MVCAD or a more complex CAD in inferior MI. Keywords: Precordial ST Segment depression, inferior myocardial infarction, SYNTAX score